2011
DOI: 10.1212/wnl.0b013e31821e54de
|View full text |Cite
|
Sign up to set email alerts
|

Resting functional connectivity between the hemispheres in childhood absence epilepsy

Abstract: Objective:The fundamental mechanisms by which childhood absence epilepsy (CAE) changes neural networks even between seizures remain poorly understood. During seizures, cortical and subcortical networks exhibit bihemspheric synchronous activity based on prior EEG-fMRI studies. Our aim was to investigate whether this abnormal bisynchrony may extend to the interictal period, using a blood oxygen level-dependent (BOLD) resting functional connectivity approach.Methods: EEG-fMRI data were recorded from 16 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 40 publications
10
73
0
Order By: Relevance
“…Brain regions with high FCS are network hubs that facilitate the integration and propagation of neural processing. 19 Increased FCS in patients with IGE is consistent with a high excitatory state or neuronal synchronization 22 and suggests that certain brain regions may be responsible for rapidly spreading the generalized spike-waves to all areas.…”
Section: Discussionmentioning
confidence: 93%
“…Brain regions with high FCS are network hubs that facilitate the integration and propagation of neural processing. 19 Increased FCS in patients with IGE is consistent with a high excitatory state or neuronal synchronization 22 and suggests that certain brain regions may be responsible for rapidly spreading the generalized spike-waves to all areas.…”
Section: Discussionmentioning
confidence: 93%
“…We found that patients in the frequent-seizure group had increased connections within the temporal lobes bilaterally involving the seizure-prone medial temporal structure and bilateral primary auditory cortex, and those in the infrequent-seizure group had increased connections of the DMN. Observations of increased connectivity with other types of epilepsy, such as in the medial temporal lobes with mesial temporal sclerosis, 8,10 the lateral orbitofrontal lobes with absence seizures, 37 and frontal lobes with idiopathic generalized epilepsy, 38,39 make us surmise that increased connections are probably more specific to understand epileptogenesis. Previous studies also pointed to a temporal lobe origin in 67%-100% of patients with HWE.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the perioral sensorimotor cortical area is a minimal neural substrate for the generation of absence seizures and myoclonus (Chen et al 2011;Fanselow et al 2001;Semba and Komisaruk 1984). The concept of focal cortical abnormality can be further supported by the elevation of interhemisphere functional connectivity of the lateral orbitofrontal cortex of patients with childhood absence epilepsy (Bai et al 2011). Rhythmic activities of the cortex and thalamic VPM are continuous throughout a SWD, and cortical neurons are phase ahead of the VPM during SWDs (Meeren et al 2002;Nicolelis et al 1995;Pinault et al 2006).…”
mentioning
confidence: 99%